2015
DOI: 10.1186/s12931-015-0285-4
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy contributes to the chemo-resistance of non-small cell lung cancer in hypoxic conditions

Abstract: BackgroundThe development of chemo-resistance in non-small lung cancer is a major obstacle in treating patients. Hypoxia is a commonly faced microenvironment in solid tumor and suggested to be related to both autophagy and chemo-resistance.MethodsIn this study, we investigated the role of hypoxia-induced autophagy in acquiring chemo-resistance in both cancer cell (A549) and human cancer tissueResultsHypoxic exposure (1 % O2) of A549 cell stimulated autophagic induction in cancer cells, shown by increase of LC3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 39 publications
2
52
0
Order By: Relevance
“…A study indicated that human lung cancer tissues that experienced chemotherapy showed increase of autophagy (22). Thus, a strategy that is specific to antiautophagy with tumor-suppressive effect would be beneficial in treating NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…A study indicated that human lung cancer tissues that experienced chemotherapy showed increase of autophagy (22). Thus, a strategy that is specific to antiautophagy with tumor-suppressive effect would be beneficial in treating NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…Dif fer ent from clas si cal types of cell death, au tophagy is con sid ered to have dual func tions in can cer, as it is both a tu mor sup pres sor and a pro tec tor of can cer cell sur vival [143]. Au tophagy is in di rectly mod u lated by meta bolic en zymes.…”
Section: Metabolic Regulation Of Cancer Cell Deathmentioning
confidence: 99%
“…Nevertheless, under stress conditions such as hypoxia and nutrient starvation, autophagy can also function as a cytoprotective mechanism that promotes cancer cell survival and resistance to chemotherapy, radiation therapy, and immunotherapy [22, 24]. Indeed, studies have shown that autophagy contributes to NSCLC chemo-resistance under hypoxic conditions [25]. High mobility group box-1 (HMGB1) protein, a DNA-binding protein that regulates cell death and survival, plays a central role in carcinogenesis [26].…”
Section: Introductionmentioning
confidence: 99%